Pendampingan Penguatan Identitas dan Pencatatan Keuangan Berbasis Excel pada UMKM Bengkel Power 7 Service - Fitriana, Nur; Ramadhani, Rezy Yulia; Pramesti, Bintang Najwa; Lestari, Gita Dwi; Hidayati, Taqwiyatul Salisa; Nabila, Cindy Salsa; Atur Sela, Az-Zahra Dian (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity aimed to improve the operational efficiency and strengthen the business identity of MSME Bengkel Power 7 Service. The main issues included manual financial records, a suboptimal business logo, and low digital visibility. The methods used were observation, interviews, training, and direct assistance. The program involved training on Excel-based financial recording, redesigning the existing logo, and registering the business location on Google Maps. The results showed significant improvements in digital bookkeeping skills, professionalism of visual identity, and online accessibility. These findings indicate that the integration of digital tools and a strong business identity can enhance the professionalism and competitiveness of MSMEs in the modern era.